A Standardized Method for Estimating the Carbon Footprint of Disposable Minimally Invasive Surgical Devices: Application in Transurethral Prostate Surgery. Issue 3 (7th September 2021) - Misrai, Vincent; Rijo, Enrique; Cottenceau, Jean-Baptiste; Zorn, Kevin C.; Enikeev, Dmitry; Elterman, Dean; Bhojani, Naeem; De La Taille, Alexandre; Herrmann, Thomas R. W.; Robert, Gregoire; Pradere, Benjamin
Abstract : Supplemental Digital Content is available in the text. Abstract : Objective: To propose a standardized methodology for estimating the embodied carbon footprint (CF) of disposable minimally-invasive surgical devices (MISDs) and their application in new benign prostatic hyperplasia (BPH) MISDs. Summary of Background Data: The estimation of the CO2e emissions of disposable surgical devices is central to empowering the healthcare supply chain. Methods: The proposed methodology relied on a partial product lifecycle assessment and was restricted to a specific part of scope 3, which comprised the manufacturing of surgical device- and non–device-associated products (NDAPs), including packaging and user manual. The process-sum inventory method was used, which involves collecting data on all the component processes underpinning disposable MISDs. The seven latest disposable MISDs used worldwide for transurethral prostatic surgery were dismantled, and each piece was categorized, sorted into the appropriate raw material group, and weighed. The CF was estimated according to the following formula: activity data (weight of raw material) × emission factors of the corresponding raw material (kg CO2e /kg). Results: The total weights of disposable packaging and user manuals ranged from 0.062 to 1.013 kg. Plastic was the most common and least emissive raw material (2.38 kg CO2e /kg) identified. The estimated embodied CF of MISDs ranged from 0.07 to 3.3 kg CO2e, of which 9% to 86% was attributed to NDAPs. Conclusions: This study described a simple and independent calculation method for estimating the embodied CF of MISDs. Using this method, our results showed a wide discrepancy in the estimated CO2 emissions of the most recent disposable MISDs for transurethral BPH surgery. Thus, the lack of CF information should be of major concern in the development of future MISDs.